Reimagining the Path of an Unmatched Orthopaedic Residency Application - Stewart A. Bryant, MD; Achraf H. Jardaly, MD; Brent A. Ponce, MD, FAOA; S. Trent Guthrie, MD, FAOA; Harris Slone, MD, FAOA; Jeremy R. Bruce, MD, FAOA; Andrew W. Wilson, MS; Charles Cody White, MD; Afshin Razi, MD; Amiethab Aiyer, MD; Andrew Sobel, MD; Anil B. Krishnamurthy, MD; et al. (JBJS Open Access, 2023)
Background:. Few evidence-based suggestions are available to help applicants and mentors improve reapplication outcomes. We sought to provide program directors' (PDs) perspectives on actionable steps to improve reapplicants' chances for a match. Methods:. The PDs were asked to rank positions unmatched applicants can pursue, steps these applicants can take for the next application cycle, and reasons why reapplicants do not match. Results:. Responses from 66 of 123 PDs were received (53.6% response rate). Obtaining new recommendation letters and rotating with orthopaedics were the highest 20 ranked steps unmatched applicants can take. No curriculum vitae (CV) improvement, poor interview, and poor letters of recommendation were the most important reasons hindering applicants from matching when reapplying. Conclusions:. Steps reapplicants could prioritize include obtaining new recommendation letters, rotating in orthopaedics, and producing new research items. CV strengthening and improving interview skills address the 2 main reasons why unmatched applicants failed in subsequent attempts. Level of Evidence:. Level IV